Independent India : the first fifty years - Karlekar, Hiranmay, 1938-; Indian Council for Cultural Relations (Delhi : Oxford University Press : Indian Council for Cultural Relations, 1998)
Covers the post-1947 period.
Includes bibliographical references.
Keywords: India -- History -- 1947-